(untitled) - Webster, Robert Grant (London, 1905)
Japanese culture has many different uniquely interesting aspects, both modern and traditional, such as: cuisine, architecture, performing arts, fashion, anime, manga and Geisha. On the one hand Japanese culture is immersed in a rich history and deep traditions dating back thousands of years; on the other Japanese society is one that is in a continual state of rapid change, and is continuously evolving with new trends in fashion, technology and pushes the boundaries of what is possible. At present, the culture of Japan stands out as one of the leading and most prominent cultures around the world, mainly due to the global reach of its popular culture. If you are looking for something different and a culture like no other you’ll certainly find that in Japan!
Keywords: Nhật Bản,Japan; Lịch sử,History